2005
DOI: 10.3748/wjg.v11.i23.3558
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the clinical, demographic and psychiatric profiles among patients with erosive and non-erosive reflux disease in a multi-ethnic Asian country

Abstract: The majority of patients who have typical symptoms of GERD have NERD or mild erosive reflux disease. Compared to patients with erosive reflux disease, patients with NERD were younger and had a higher prevalence of minor psychiatric morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
3
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
4
35
3
2
Order By: Relevance
“…Other authors reported individuals with complicated reflux disease being older than patients with NERD+, although the latter were actually much the same age as the group with ERD, as in our population [14] . We also found no gender-related differences in our two patient groups despite the literature reporting a tendency to find more females among NERD patients than among cases of esophagitis [12,15,16] . In our study population, the presence of hiatal hernia was associated more frequently with a picture of reflux with esophagitis.…”
Section: General Considerations: Study Populationcontrasting
confidence: 54%
See 1 more Smart Citation
“…Other authors reported individuals with complicated reflux disease being older than patients with NERD+, although the latter were actually much the same age as the group with ERD, as in our population [14] . We also found no gender-related differences in our two patient groups despite the literature reporting a tendency to find more females among NERD patients than among cases of esophagitis [12,15,16] . In our study population, the presence of hiatal hernia was associated more frequently with a picture of reflux with esophagitis.…”
Section: General Considerations: Study Populationcontrasting
confidence: 54%
“…In particular, the fact that the mean age of the ERD group was similar to that of the NERD+ patients (around 50 years old in both cases) seems to contradict the claim that patients with- out esophagitis tend to be younger and can be expected to progress towards a picture of full-blown esophagitis as they grow older [12,13] . Other authors reported individuals with complicated reflux disease being older than patients with NERD+, although the latter were actually much the same age as the group with ERD, as in our population [14] .…”
Section: General Considerations: Study Populationmentioning
confidence: 62%
“…Table 2 shows a summary of four studies that reported the prevalence of NERD among patients with GERD symptoms presenting to upper endoscopy [5,6,7,8]. The reported prevalence ranged between 36.7 and 86.6%.…”
Section: Prevalence Of Nerdmentioning
confidence: 99%
“…7 In daily practice, while GERD is often established as a non-severe case, it can be a serious disease with very high rate of medical and non-medical complications including Barrett's esophagus, malignancy, socio economic burden, and declined quality of life. 8 In the current standard, ambulatory esophageal pH monitoring remains unsatisfying as a gold standard so that the patients' medical history with/without endoscopic examination still plays a major role in the diagnosis. 9 GERD-questionnaire (GERDQ) includes reference questions comprised of typical and atypical symptoms of the disease for GERD-suspected patients and it is a simple diagnostic tool to be used in primary health care.…”
mentioning
confidence: 99%
“…Adapun lama DM,[2][3][4][5][6][7][8][9][10][11][12][13] p = 0,976), obesitas (37% vs 38%, p = 0,897), usia (53,2 ± 10,5 vs 54,7 ± 9,3, p = 0,481) …”
mentioning
confidence: 99%